2018
DOI: 10.1093/jac/dky481
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics and pharmacokinetics of CNS penetration of efavirenz and its metabolites

Abstract: Background: There are limited data on the pharmacogenetics and pharmacokinetics of the CNS penetration of efavirenz. Objectives: We investigated genetic polymorphisms associated with CSF concentrations of efavirenz and its metabolites and explored the relationships with neurocognitive performance. Methods: We included 47 HIV-infected South African black adults with and without HIV-associated neurocognitive disorder on efavirenz/tenofovir/emtricitabine and collected paired plasma-CSF samples. We considered 2049… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…Several clinical studies on African populations ( Table 1 ) have demonstrated the potential for PGx testing and dose adjustments in HIV patients receiving Efavirenz [ 26 , 27 , 28 , 30 , 41 , 42 ]. Other clinical studies have identified PGx biomarkers for African patients receiving rosuvastatin [ 43 ], imatinib [ 44 ], anti-retroviral (ARV) therapy, TB, and antimalarial comedication [ 25 , 45 , 46 , 47 ].…”
Section: Paucity Of Clinical Pharmacogenetics Studies In Ssamentioning
confidence: 99%
See 2 more Smart Citations
“…Several clinical studies on African populations ( Table 1 ) have demonstrated the potential for PGx testing and dose adjustments in HIV patients receiving Efavirenz [ 26 , 27 , 28 , 30 , 41 , 42 ]. Other clinical studies have identified PGx biomarkers for African patients receiving rosuvastatin [ 43 ], imatinib [ 44 ], anti-retroviral (ARV) therapy, TB, and antimalarial comedication [ 25 , 45 , 46 , 47 ].…”
Section: Paucity Of Clinical Pharmacogenetics Studies In Ssamentioning
confidence: 99%
“…Distinct and highly diverse alleles of the Cytochrome P450 family have been recorded in African populations relative to other populations, highlighting the need for further dedicated PGx and functional studies on these unique variants [ 21 ]. For instance, the loss-of-function CYP2B6*6 allele which accounts for low efavirenz plasma levels and an increased risk of neurotoxicity, is highly prevalent in African populations relative to Europeans and Asians [ 30 ].…”
Section: Challenges In Genotyping Pharmacogene Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported LD plots for these polymorphisms. 18 …”
Section: Methodsmentioning
confidence: 99%
“…17 We previously reported on the pharmacogenetics of CSF penetration of efavirenz in black South Africans. 18 Here, we characterise the associations between transporter gene polymorphisms and CSF penetration of tenofovir and emtricitabine in the same cohort.…”
Section: Introductionmentioning
confidence: 99%